2009
DOI: 10.1159/000228076
|View full text |Cite
|
Sign up to set email alerts
|

Association of Secondary Hyperparathyroidism with CKD Progression, Health Care Costs and Survival in Diabetic Predialysis CKD Patients

Abstract: Background/Aims: The objective of this study was to examine health care costs and utilization and the risks of dialysis or mortality among diabetic predialysis chronic kidney disease (CKD) patients with and without secondary hyperparathyroidism (SHPT). Methods: This retrospective, matched cohort study examined insurance claims from 703 adult diabetic predialysis CKD patients with and without SHPT during a 72-month follow-up period. Annualized estimates of health care service utilization, costs and disease prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 25 publications
(16 reference statements)
2
33
1
1
Order By: Relevance
“…Similar results indicating that secondary hyperparathyroidism is a risk factor associated with progression to dialysis or death have been obtained in cohort studies of the health costs of CKD in pre-dialysis patients [9,10]. …”
Section: Clinical Studies and Biological Plausibilitysupporting
confidence: 80%
“…Similar results indicating that secondary hyperparathyroidism is a risk factor associated with progression to dialysis or death have been obtained in cohort studies of the health costs of CKD in pre-dialysis patients [9,10]. …”
Section: Clinical Studies and Biological Plausibilitysupporting
confidence: 80%
“…In a large series of 602 CKD patients, Tanaka and co-workers have shown an independent association between diabetes and high phosphate levels as well as low PTH, FGF-23, and vitamin D levels (29). The consequent expansion of the phosphorus pool, coupled with a poor vitamin D status, might contribute to acceleration of arterial function and structure deterioration as well as explain the excessive risk of all-cause mortality associated with hyperphosphatemia in patients with diabetes (30,31).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SHPT is associated with a faster rate of CKD progression [36]. The meta-analysis suggested that every 1 mg/dL increase in serum Pi was independently associated with an increased risk for kidney failure (HR 1.36; 95% CI 1.20–1.55) [37].…”
Section: Discussionmentioning
confidence: 99%